To determine the frequency of necrotizing enterocolitis in preterm infants treated with prophylactic probiotics versus controls - Hasham, Amal; Zulfiqar, Sughra; Asif, Annam; Ayub, Ammara; Fayyaz, Faiza; Idris, Arooba (Journal of Rawalpindi Medical College, 2025)
Objective: To determine the frequency of necrotising enterocolitis in preterm infants treated with prophylactic probiotics versus controls. Methodology: This was a Quasi experminet, conducted in Holy Family Hospital Rawalpindi, Department of Paediatrics from Jan 2020 to Dec 2020. A total of 170 preterm neonates (gestational age 30–35 weeks, birth weight <1500 g) were enrolled and randomly divided into two groups: Group A received prophylactic probiotics, while Group B received routine management without probiotics. Both groups followed standard feeding protocols using expressed breast milk or preterm formula, gradually advancing feeds as tolerated. NEC was monitored clinically and radiologically and confirmed by pneumatosis intestinalis. The study endpoints included NEC incidence with follow-up until 10 days of life or discharge. Data were analysed using SPSS 23, with chi-square tests applied post-stratification for variables such as gestational age, gender, and weight. A p-value of <0.05 was considered statistically significant. Results: Comparison of frequency of necrotising enterocolitis in preterm infants treated with prophylactic probiotics versus controls shows 4.71%(n=4) NEC in Group A and 18.82%(n=16) in Group B. Conclusion: The frequency of necrotizing enterocolitis in preterm infants treated with prophylactic probiotics is lower when compared with controls Keywords: Preterm, probiotics, necrotising enterocolitis